Strengthening the Micro Teaching Role in the Development of Teacher Candidates Teaching Skills - Subur, Subur; Sumiarti, Sumiarti; Fatmawati, Julia; Aisyah, Puji Nur; Khomsah, Banatul (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
This study aims to analyze the micro-teaching course at the Faculty of Tarbiya and Teacher Training (FTIK) IAIN Purwokerto. The laboratories department of FTIK carried out the program. Analyzing its implementation is essential because micro-teaching is a strategic activity to improve teacher competence. Micro teaching is widely associated with efforts to improve teacher skills in education, and thus great attention is required. The data source in this study is the micro-teaching manager and the study program head. It is from observations and interviews. The steps to analyze the data are reduction, data display, verification, and conclusions. The results showed that technical briefing by merging all study programs at the same time, overcrowded participants, unrepresentative speakers for each study program, irrelevant appointed supervisors with the study program, and micro-teaching schedules that coincide with the lectures schedules had the potential to cause the implementation of micro-teaching becomes less effective. It encourages the need to re-enforce the role of micro-teaching to be more effective in providing basic teaching skills for the teacher candidates. The lecture should manage every study program by coordinating with the laboratory. It aims to increase the effectiveness of micro-teaching. The briefing material needs to be supplemented by enrichment various learning strategies relevant to the study program. One lecturer with small classes carries out lectures according to the norms of micro-teaching classes, and the frequency of meetings is adjusted to the regular lecture schedule.